A versatile transapical device for aortic valvular disease: One-year outcomes of a multicenter study on the J-Valve system. Issue 5 (November 2018) - Tung, Mingwui; Wang, Xu; Li, Fei; Wang, Hao; Guo, Yingqiang; Wang, Chunsheng; Wei, Lai; Luo, Xinjin; Wang, Xin; Wang, Wei
Highlights: Transapical-transcatheter aortic valve implantation is a reasonable option in patients considered poorly suitable for surgical aortic valve replacement. The one-year follow-up of the J-Valve demonstrated excellent and sustained hemodynamic results. Longer-term follow-up data are needed to determine the wider clinical utility of this device. Abstract: Background: The novel J-Valve (JC Medical Inc, Burlingame, CA, USA) was developed to cope with aortic valvular disease by facilitating accurate positioning. We present the first one-year results regarding the safety and efficacy of the J-Valve system implantation in patients with severe aortic stenosis (AS) or aortic regurgitation (AR) undergoing transapical-transcatheter aortic valve implantation. Methods: This prospective multicenter study enrolled 107 high-risk patients (mean age 74.4 ± 5.2 years; mean EuroSCORE-I 11.2 ± 1.2%) with severe AS ( n  = 64) or AR ( n  = 43), at the three largest cardiac centers in China. The study was fully monitored, and adverse events were adjudicated by an independent clinical events committee using Valve Academic Research Consortium criteria. Results: The success rate of the procedure was 91.6% (98/107). At 1 year, the all-cause mortality was 5.0%, stroke 2%, and rate of new pacemakers 5.0%. Only mild paravalvular leak was reported. Among the patients with AS, the 1-year follow-up demonstrated a sustainable reduction of mean transaortic gradient from 57.7 ± 15.4 mmHg to 15.5 ± 8.3 mmHg. All patients who completed the follow-up reported improvements in New York Heart Association functional class ( n  = 93) and health-related quality of life as assessed by the EuroQol five dimensions questionnaire index ( n  = 94). In intergroup comparisons, the 1-year major adverse cardiovascular events-free survival was similar between the groups based on valve disease (AS vs. AR, log-rank p  = 0.17) or morphology (tricuspid vs. bicuspid aortic valve, log-rank p  = 0.25). Conclusions: Our study provides further evidence on the safety and efficacy of the J-Valve in high-risk patients with AS or AR for surgery.